Adultery Crimes From The Perspective Of Islamic Law And Customary Law In Dolok District, North Padang Lawas Regency - Perantoan Rambe; Sahmiar Pulungan (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
Violation of Islamic law and customary criminal law is still viewed as something that can cause disruption and disturb the consciousness of the community. The purpose of this research is to examine and analyze legally how the regulation of adultery is based on Islamic law and customary law in Dolok District, Padang Lawas Utara Regency, to understand and analyze legally the application of customary criminal sanctions against perpetrators of adultery in Dolok District, Padang Lawas Utara Regency, and to examine the authority of customary leaders in resolving cases of adultery in Dolok District, Padang Lawas Utara Regency. The type of research used is qualitative research with data collection techniques, including interviews with customary leaders in Dolok District, Padang Lawas Utara Regency. The results of this study indicate that the regulation of customary sanctions for adultery in customary law is called "appeal dila," which is a type of punishment that requires the perpetrator to slaughter a goat/buffalo/cow by inviting the community to gather and have a communal meal as a basis for seeking forgiveness for the act of adultery. The application of customary sanctions against adulterers involves punishment imposed by the customary leaders, namely Raja Panusunan Bulung and Raja Pamusuk, after a customary meeting attended by Mr Namalim (Religious Figure), Datu (Health Doctor), Pangatak-Pangetong/Rokkaya (Traditional Healers), panyujukan burger (Betel Leaf Carrier), Halakna Dihuta (Village Community), and the prepared sanctions.